ELEMEN INTANGIBLE ORGANISASI DAN KINERJA ORGANISASI: KAJIAN EMPIRIS RESOURCE BASED VIEWS PADA ORGANISASI PEMERINTAHAN DAERAH - M. Irhas Effendi M. Irhas Effendi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2011)
To realize good governance during the era of autonomy from local government, better performance by the local government is crucially required. In order to achieve better performance, a strategic plan is needed taking into account all available resources. Important resources which gain a little attention in practice and research on public sectors are intangible resources. This research is aimed to examine of the impact of five intangible organization resources elements, independently and interactions among them on organizational performance in public sectors. The data is collected from 82 samples of a local government institution authorities of echelons III in Yogyakarta. Multiple Regression and moderating multiple regression are used to test the hypotheses. The results indicate that all intangible organization elements (managerial capabilities, human capital, internal auditing, labor relations, and organizational culture) have a positive impact on organizational performance. The results examining the interaction among intangible organization elements have a positive impact on organization performance in different dimensions. The findings implicate that intangible organization elements are important to support public organization performance.